Descriptive norms and entrepreneurial intentions: the mediating role of anticipated inaction regret - Bae, Tae Jun; Lee, Chong Kyoon; Lee, Younggeun; McKelvie, Alexander; Lee, Woo Jin (Frontiers in Psychology, 2024)
Current research uses the cognitive-based Theory of Planned Behavior (TPB) model to predict entrepreneurial intentions. However, given the close relationship between cognitions and emotions, researchers may need to pay more attention to how emotional reactions help predict entrepreneurial intentions. This study examines the additional cognitive and emotional predictors: descriptive norms and anticipated inaction regret to increase the predictive power to explain entrepreneurial intentions.This study employs the affect-as-information perspective as a complementary theoretical lens to TPB to test whether the role of descriptive norms on entrepreneurial intentions is affected by anticipated inaction regret as a form of emotional reaction to descriptive social norms. This paper conducted two survey-based studies with diverse samples (i.e., online Mturk panels of adults in America and undergraduate students in Korea). This study demonstrates (1) a positive and significant relationship between descriptive norms and entrepreneurial intentions and (2) a mediating role of anticipated inaction regret between descriptive norms and entrepreneurial intentions. The results contribute to the entrepreneurial intentions literature by exploring the mechanism between cognition and emotion and highlighting an indirect emotional link (e.g., anticipated inaction regret) in understanding entrepreneurial intentions.